Comparison of joint effect of acute and chronic toxicity for combined assessment of heavy metals on Photobacterium Sp.Naa-Mie - Adnan, Nur Adilah; Effendi Halmi, Mohd Izuan; Abd Gani, Siti Salwa; Zaidan, Uswatun Hasanah; Abd Shukor, Mohd Yunus (Multidisciplinary Digital Publishing Institute, 2021)
Predicting the crucial effect of single metal pollutants against the aquatic ecosystem has been highly debatable for decades. However, dealing with complex metal mixtures management in toxicological studies creates a challenge, as heavy metals may evoke greater toxicity on interactions with other constituents rather than individually low acting concentrations. Moreover, the toxicity mechanisms are different between short term and long term exposure of the metal toxicant. In this study, acute and chronic toxicity based on luminescence inhibition assay using newly isolated Photobacterium sp.NAA-MIE as the indicator are presented. Photobacterium sp.NAA-MIE was exposed to the mixture at a predetermined ratio of 1:1. TU (Toxicity Unit) and MTI (Mixture Toxic Index) approach presented the mixture toxicity of Hg2+ + Ag+, Hg2+ + Cu2+, Ag+ + Cu2+, Hg2+ + Ag+ + Cu2+, and Cd2+ + Cu2+ showed antagonistic effect over acute and chronic test. Binary mixture of Cu2+ + Zn2+ was observed to show additive effect at acute test and antagonistic effect at chronic test while mixture of Ni2+ + Zn2+ showing antagonistic effect during acute test and synergistic effect during chronic test. Thus, the strain is suitable and their use as bioassay to predict the risk assessment of heavy metal under acute toxicity without abandoning the advantage of chronic toxicity extrapolation.